Emprego de espectrometria no infravermelho e métodos quimiométricos para a identificação e quantificação de petróleos a partir de misturas de frações de diesel - Rocha, Júlia Tristão do Carmo (2009)
The knowledge of the petroleum`s composition and its products is an essential necessity in a refinery for the adjustment of the process conditions. The infrared spectrometry, associated to chemometrics tools, has been presented as a useful tool to take care of this necessity for its great potentiality and applications. In such a way, due to applicability of the chemometrics tools, in this work the discrimination for PCA (principal components analysis) and the quantification for intervals partial least square (iPLS), for sinergism of intervals (siPLS) and for principal components regression (PCR) of three fractions of destillation are proposals, proceeding from three different petroleums (A, B and C), in the band of diesel attainment (210ºC 260º C approximately) from the absorption in the medium infrared (MIR). For that, 150 mixtures of the 3 fractions were produced, varying it enters 0 and 1,33% between a sample and another one. Later, specters were gotten, in the region of the MIR, of all the produced mixtures and after that the data were submitted to the chemometrics analyses. 100 samples were used for the calibration of model and 50 for its validation. First it was carried through the analysis for principal components and from it it was possible to discriminate the samples in accordance with its predominant fraction. xiAfter the identification of the samples, it was continued in the attempt of if quantifying the 3 fractions, individually and simultaneously, in each one of them through the application of the methods iPLS, siPLS and PCR. The gotten models had been, then, evaluated for its the R2, the RMSEP and the number of latent variable (VL) or principal components (PC) used. iPLS, siPLS and PCR models were also developed for the determination of the samples density and viscosity, which were evaluated in the same way. All the generated models had gotten resulted sufficiently satisfactory. However comparing the models siPLS and iPLS, it was verified that it did not have significant difference between them not justifying, therefore, the use of the models siPLS. About the models generated for PCR, the same ones had also gotten resulted sufficiently next to supplied for the method iPLS not having a justifiable preference in the choice between a method and another one. With this, it demonstrates, therefore, that it is possible to discriminate and to quantify petroleums of distinct origins from its fractions using spectrometry in the region of the MIR and chemometrics techniques